Unraveling the coupled HighResMIP-CMIP6 models resolution impacts in present climate and future projections of water availability over South America - da Silva, Nilson Oliveira; da Rocha, Rosmeri Porfírio; Nunes, Ana Maria Pereira (Frontiers in Earth Science, 2025)
This study examines present and future projections of precipitation and evapotranspiration for South America, focusing on small regions with distinct environmental and climatic characteristics. The objective is to understand future water availability across the continent and assess the role of model resolution in shaping these projections (2015–2050). Five coupled Global Coupled Climate Models (GCMs) from CMIP6 (HighResMIP) with low (∼70 km) and high (∼25 km) horizontal resolutions were analyzed: HadGEM3, MPI, CMCC, EC-Earth3P, and HiRAM. For the present climate (1979–2014), statistical indices were applied to identify the primary effects of model resolution on the ability to capture regional climate characteristics by comparing simulations with GPCC and ERA5 reference dataset. The HighResMIP models demonstrated strong performance in simulating the precipitation climatology, with higher-resolution versions increasing the spatial pattern correlation (until 0.90) and reducing the RMSE (1.32 to 1.82 mm/day) and biases. These spatial correlations improved further (until 0.93) when only precipitation over continental areas is analyzed. At the regional scale, the precipitation annual cycles in high-resolution simulations is consistently improved over the northeast Brazil, La Plata basin and eastern Amazon basin, while in others regions the differences between high and low resolutions are smaller as well as occurs for evapotranspiration annual cycles except in eastern Amazon. In both resolutions, projections indicate a future intensification of the dry season, with a rainfall decrease of over 30% in central South America. For austral summer and autumn, a future increase of rainfall is projected for Pacific and Atlantic branches and southward of 25°S, including La Plata basin. The future changes in water resources present some differences associated with model resolution. The high-resolution projects water resources increased in an extensive strip from central Argentina to northeastern Brazil and decreased over the Amazon basin. For low-resolution projections this change pattern is not so evident due large divergence between members. The signal of precipitation and evapotranspiration trends controlling the water resources trends at a regional scale, previously found only in regional climate projections, is consistent with those in high-resolution HighResMIP simulations.